Automated scheduling and scientific management of copper smelters. (2nd January 2016) - Navarra, A.
Abstract : The Altonorte Smelter implemented a daily scheduling algorithm in 2013, which has now been generalised for all conventional copper smelters. It applies a combinatorial search, in which the possible converter feeding sequences are evaluated using a greedy heuristic; the daily schedule is then constructed using the heuristically optimal sequence. Depending on the mode of operation, the objective may be to maximise copper production, maximise profits or control concentrate stockpiles. This combinatorial greedy approach has been incorporated within discrete event simulations, which mimic hundreds of days of operation, hence analysing alternate modes of operation. Automated scheduling is fundamental to the scientific management of copper smelters, as scheduling parameters characterise the operational modes.